NICKEL EXTRACTION FROM LOW GRADE SAPROLITE ORE BY ROASTING AND LEACHING PROCESS IN SULFURIC ACID SOLUTION UNDER ATMOSPHERIC PRESSURE - DILASARI (NIM : 12506001), BONITA
Pirometallurgical- hydrometallurgical route has proved to be capable to extract nickel and cobalt nickel lateritic ore, for example using the Caron process. Based on the Ellingham diagram, NiO will be more difficult to be reduced to Ni compared to that of Fe2O3 to Fe3O4, because the equilibrium line of NiO formation is laid below the equilibrium line of Fe2O3 formation. However, the reduction of Fe3O4 to FeO and FeO to Fe at temperatures ≤ 10000C is more difficult than that of NiO to Ni and CoO to Co. Therefore, by adjusting the oxygen reduction potential within the furnace, selective reduction can be performed which results in the reduction of Fe2O3 and Fe (III) hydroxide is reduced only to be Fe3O4, but Ni and Co can be reduced to a metal form. LGSO reduction roasting experiments have been conducted at various temperatures (8000C-10000C), time (15-80 minutes) and concentration (0-30%) of residual oil used as reducing agent. This process is followed by the oxidation leaching process in an excess sulfuric acid solution purged by air. Kinetics study of leaching process has conducted at 500C, 600C, 700C and 800C in 1M sulfuric acid solution. From the experimental results observed, it is indicated that the best condition for roasting reduction is 9500C, for 40 minutes, using residual oil 20% by weight of the dried ore. The study indicates the leaching process can be presented by the shrinking-core model and it is found the overall rate is controlled by the rate of diffusion through the diffusion layer in the fluid with an activation energy of 4.5697 kcal / mol. This may caused by the rate of mass transfer of dissolved oxygen from the bulk of solution to the particle surface. Percentage of Ni extraction that can reach 94.34% and the percentage of impurities Fe, Mg and Al dissolution are respectively 73.08%, 100% and 82.43%. The results have exhibited that the percentage of Co extraction which varies greatly due to the uneven distribution of the element in the LGSO. Although this method can yield high percentage of Ni extraction, the selectivity of process is inadequate.